Intra-Household and Close-Contact SARS-CoV-2 Transmission Among Children – a Systematic Review - Spielberger, Benedikt D.; Goerne, Tessa; Geweniger, Anne; Henneke, Philipp; Elling, Roland (Frontiers in Pediatrics, 2021)
Introduction: The outbreak of the novel coronavirus disease (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to a range of emergency measures worldwide. Early in the pandemic, children and adolescents were suspected to act as drivers of the COVID-19 spread in the population, which was based on experiences with influenza virus and other respiratory pathogens. Consequently, closures of schools and kindergartens were implemented in many countries around the world, alongside with other nonpharmaceutical interventions for transmission control. Given the grave and multifaceted consequences of contact restriction measures for children, it is crucial to better understand the effect size of these incisive actions for the COVID-19 pandemic. Therefore, we review the current evidence on transmission of SARS-CoV-2 to and by children. Data Sources: PubMed and preprints uploaded on medRxiv. Study selection: Original research articles, case reports, brief communications and commentaries were included into the analysis. Each title or abstract was independently reviewed to identify relevant articles. Studies in other languages than English were not included. Data extraction: Two reviewers independently reviewed the selected studies. Extracted data included citation of each study, type of healthcare setting, location of the study, characteristics of patient population and reported outcomes. Results: Data on transmission of SARS-CoV-2 on or by children is scarce. Several studies show a lower seropositivity of children compared to adults, suggesting a lower susceptibility of especially younger children. Most insight currently comes from household studies suggesting, that children are predominantly infected by their household contacts. The contagiousness however, seems to be comparable between children and adults, based on our meta-analysis of included studies. Conclusions: Larger and systematic studies are urgently needed to better understand the age dependent patterns of SARS-CoV-2 transmission and thereby design more effective non-pharmaceutical interventions to reduce disease transmission.